Integration of Photonic Circuits in Electronics for Enhanced Data Processing and Transfer - Chetan, Anjna (Journal for Research in Applied Sciences and Biotechnology, 2022)
The rapid growth of data-intensive applications, such as artificial intelligence (AI), big data analytics, and cloud computing, has highlighted the limitations of traditional electronic circuits, particularly in terms of data transfer rates, processing power, and energy efficiency. This study explores the integration of photonic circuits with electronic systems as a viable solution to these challenges. By leveraging the speed and efficiency of photons for data transmission, photonic circuits promise substantial improvements over conventional electronic circuits. The research employs a mixed-method approach, combining experimental analysis with a comprehensive literature review. Experimental results demonstrate that hybrid photonic-electronic circuits can achieve up to ten times faster data processing speeds, a 30% reduction in power consumption, increased bandwidth, and reduced latency compared to traditional electronic systems. These advancements address key issues such as resistive losses and heat generation, offering enhanced performance for high-demand applications. However, challenges related to signal conversion and thermal management persist. Future research is needed to refine photonic-electronic integration and explore advanced technologies, including quantum photonics, to further enhance data processing capabilities. Overall, the study highlights the significant potential of photonic circuits to revolutionize data systems, providing a path towards next-generation computing technologies.